2022
DOI: 10.1111/ijfs.15875
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alternating magnetic field on the quality of fresh‐cut apples in cold storage

Abstract: This study evaluated the inhibitory effect of alternating magnetic field (MF) on enzymatic browning, physicochemical properties and microbial proliferation of fresh-cut apples during cold storage. The results showed that after 9-day storage, the browning index of apple slices increased by 174.07% in the conventional refrigerated group but by only 132.32% in the alternating MF group, the total number of colonies in the alternating MF group was 1.32 log CFU g −1 , less than that in the conventional refrigerated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“… Yang et al (2020) reported that magnetic field could delay the ripening of cherry tomato and keep its quality during storage. Lv et al (2022) found that magnetic field (2 mT, 50 Hz) could maintain better color and firmness of fresh-cut apples during 9 d storage at 4 °C. It was also reported that polyphenol oxidase activity and MDA accumulation of bananas under magnetic field treatment (2 mT, 60 Hz) were lower during 10 d storage ( Zhao et al, 2021 , Zhao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 95%
“… Yang et al (2020) reported that magnetic field could delay the ripening of cherry tomato and keep its quality during storage. Lv et al (2022) found that magnetic field (2 mT, 50 Hz) could maintain better color and firmness of fresh-cut apples during 9 d storage at 4 °C. It was also reported that polyphenol oxidase activity and MDA accumulation of bananas under magnetic field treatment (2 mT, 60 Hz) were lower during 10 d storage ( Zhao et al, 2021 , Zhao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 95%